Sex differences involved in persistent atrial fibrillation recurrence after radiofrequency ablation - Haiwei Li; Zefeng Wang; Zichao Cheng; Yingming Zhu; Zhongyu Yuan; Jianwei Gao; Xiaoping Zhang; Yongquan Wu (BMC Cardiovascular Disorders, 2022)
Abstract Background In recent years, the difference in outcomes of radiofrequency catheter ablation (RFCA) in persistent atrial fibrillation patients has risen. In particular, biological sex seems involved in a different response to the AF ablation procedure. In our study, we analyzed the AF recurrences after RFCA assessing the other association between male/female patients with the outcomes. Methods We enrolled 106 patients (74.5% men) with persistent atrial fibrillation with scheduled follow-up. The baseline clinical characteristics and AF recurrence after RFCA were compared between men and women. Cox regression analyses were performed to determine the risk predictors of AF recurrence. Results The proportion of RFCA in women was lower than that in men. Men with persistent AF were younger than women (58.6 ± 10.4 years vs. 65.1 ± 8.7 years, respectively; p = 0.003). The left atrium (LA) diameter was higher in males (43.7 ± 4.6 mm vs. 41.3 ± 5.5 mm; p = 0.028), and the level of left heart ejection fraction (LVEF) was higher in females (59.4 ± 6.9% vs. 64.1 ± 5.5%; p = 0.001). Sex differences in AF recurrence after RFCA were significant during the median 24.4-month (interquartile range: 15.2–30.6 months) follow-up period, and the recurrence rate of AF in women was significantly higher than that in men (p = 0.005). Univariable Cox regression analysis showed that female sex was a risk factor for persistent AF recurrence after RFCA [HR: 2.099 (1.087–4.053)]. Univariate Cox regression analysis revealed that non-PV ablation not associated with AF recurrence [HR: 1.003 (0.516–1.947)]. Conclusion In a monocentric cohort of persistent AF patients, the female biological sex was associated with a higher risk of AF recurrence after RFCA.